(untitled) (Journal of European Studies (JES), 2025)
Simone de Beauvoir’s The Second Sex (1949) is one of the most important works of feminist theory, which explains how women are constructed as the “Other” in a patriarchal society. However, while her philosophical and sociological insights have been extensively analyzed by scholars, the linguistic dimensions of her work, particularly the ways in which women’s voices are represented, muted, or limited, have been relatively neglected. This article examines the linguistic frameworks within The Second Sex, focusing on (1) how Beauvoir’s language constructs or limits female agency, (2) the role of gendered vocabulary in reinforcing binary structures, (3) existentialist interpretations of gendered discourse, (4) the overlooked linguistic agency of women in Beauvoir’s work, and (5) the implications of her work for contemporary feminist linguistics. This research aims to discusses how The Second Sex reveals and sometimes reinforces the marginalization of women’s speech by combining linguistics and existentialist philosophy principles. This paper suggests that post-structuralist and intersectional feminist linguistics can build on Beauvoir’s ideas in today’s world.